2005
DOI: 10.1148/radiol.2342040119
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Angioplasty and Stent Placement: Comparison of Transcranial Doppler US Data and Clinical Outcome with and without Filtering Cerebral Protection Devices in 509 Patients

Abstract: Carotid angioplasty and stent placement yielded more microemboli in patients treated with filtering CPDs than in unprotected procedures. The infrequent occurrence of cerebral sequelae did not allow comprehensive statistical comparison between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 34 publications
2
84
0
1
Order By: Relevance
“…It is well-known that the highest potential for embolization occurs post-stent placement when the balloon crushes the plaque against the stent struts. 24,25 In our series, the 30-day composite rate of any stroke or death was 1.2% (0.8% for symptomatic and 0.4% for asymptomatic patients). These results are considerably below the 3% and 6% of maximum complication rates recommended in the American Heart Association guidelines for carotid endarterectomy of asymptomatic and symptomatic patients, respectively, 17 and compare favorably with rates found in patients enrolled in large trials of carotid stent placement (10% in the Carotid and Vertebral Artery Transluminal Angioplasty Study, 26 12.1% in the WALLSTENT [carotid stenting versus endarterectomy in patients with symptomatic carotid stenosis] trial, 27 4.8% in the Stenting and Angioplasty with Protection in Patients at High Risk for Endarterectomy study, 4 6.8% in the Stent-Protected Angioplasty versus Carotid Endarterectomy trial, 2 and 9.6% in the EVA-3S [endarterectomy versus stenting in patients with symptomatic severe carotid stenosis] study 1 ).…”
Section: Discussionmentioning
confidence: 54%
“…It is well-known that the highest potential for embolization occurs post-stent placement when the balloon crushes the plaque against the stent struts. 24,25 In our series, the 30-day composite rate of any stroke or death was 1.2% (0.8% for symptomatic and 0.4% for asymptomatic patients). These results are considerably below the 3% and 6% of maximum complication rates recommended in the American Heart Association guidelines for carotid endarterectomy of asymptomatic and symptomatic patients, respectively, 17 and compare favorably with rates found in patients enrolled in large trials of carotid stent placement (10% in the Carotid and Vertebral Artery Transluminal Angioplasty Study, 26 12.1% in the WALLSTENT [carotid stenting versus endarterectomy in patients with symptomatic carotid stenosis] trial, 27 4.8% in the Stenting and Angioplasty with Protection in Patients at High Risk for Endarterectomy study, 4 6.8% in the Stent-Protected Angioplasty versus Carotid Endarterectomy trial, 2 and 9.6% in the EVA-3S [endarterectomy versus stenting in patients with symptomatic severe carotid stenosis] study 1 ).…”
Section: Discussionmentioning
confidence: 54%
“…Thus, DPDs themselves harbor the potential to cause distal thromboembolic complications, 11,15 explaining the increased rate of microembolic signals on transcranial Doppler sonography in patients in whom a DPD had been used. 11,26 We noted a high (67%) incidence of ICA iatrogenic vasospasm associated with the use of the first-generation FilterWire DPD in the current study, which necessitated the modification of the conventional procedure to include intraarterial infusion of nitroglycerin in 3 cases and periods of pause in order to wait for the vasospasm to resolve before proceeding to the next step.…”
Section: Discussionmentioning
confidence: 78%
“…Some authors have found a higher rate of microembolism by transcranial Doppler in CAS with protective devices than in CASWPD. 30 A higher rate of cerebral ischemic lesions on DWI associated with the use of protection devices has also been found. 31,32 Finally, it has been estimated that cerebral protection devices prevent only 25% of clinical embolisms.…”
Section: Figmentioning
confidence: 96%